PRESUPPOSITION IN BEAUTY AND THE BEAST MOVIE SCRIPT - Yossi Kristy; Deliana Deliana; Yulianus Harefa (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
This research was intended to find out the types of presupposition in the character’s utterances of Beauty and the Beast movie script and describe the meaning of presupposition that are represented in the movie script. This research used a descriptive qualitative method, which was carried out by collecting, grouping, analyzing and interpreting the research data. The data in this research were the utterances of the characters in movie script containing presupposition. The data were collected through four steps:  observation, taking note, data validation and setting them in tables. Based on the data analysis, it was found that 6 types of presupposition were used in the character’s utterances of the movie script. The most frequent type of presupposition used by the characters was existential presupposition with 26 data of 58 data found in this movie script. The second type of presupposition often used was factive presupposition with 9 data found in the data. Then, the third was lexical presupposition consisting of 8 data and the fourth was structural presupposition with the same number. The fifth type of presupposition used was non-factive presupposition with 4 data found in this research. The last type of presupposition used in this research was counter-factual presupposition with 3 data found in the movie script.